ANTIOKSIDAN DALAM MASAKAN MINANG DAN POTENSI PROTEKTIF TERHADAP RISIKO PENYAKIT KARDIOVASKULAR - Helmizar Helmizar; Fasli Djalal; Nur Indrawati Lipoeto (Jurnal Kesehatan Masyarakat Andalas, 2009)
Cardiovascular disease (CVD) is aprimary cause of death in Indoensia nowaday. Development of CVD is caused by some determinant factors, as well as nutrient and non-nutrient intake to result of oxidative stress in the body. Antioxidants, such as vitamin E, beta-caroten, vitamin C andflavonoid, are able to neutralize the effect of free radical from oxidative stress and to influence lipid plasma. The objective of this study was to know the level of antioxidant intake and its association with blood lipid among Minangkabau ethnic. A cross sectional study was conducted in Padang ciry. The study population was adult, age 30 -65 years old, and sampling technique was multistage random sampling, and sample size is 215 respondents. Data collected were demographic characterisitics, food intake using semi quantitative food frequency questionnaire (SMFFQ) and anthropometric measurements. Blood samples were collected to assess plasma lipid profile and level of flavonoid. Data was analyzed with SPSS version 12 and modifiedNutriSurvey Indonesia. The results showed that the average intake of flkaroten was 15.0 ( SD 6. 7) mg/dcry, vitamin C was 66. 3 (SD 30.6) mg/day, vitamin E was 17,8 (SD 11.8) mg/day and flavonoid was 105.0 (SD 48.1) mg/day. The level, offlavonoid from Minang traditional food was highfrom "gulai" which consisted of some vegetables, such as cassava leaf and jack fruit leaf, and from "samba lado " which consisted of red pepper, union, garlic andsame traditional spices. The mean of total cholesterol, LDL cholesterol were above normal but the mean of HDL cholesterol, trigliserides, and ratio of cholesterol to LDL/HDL were within normal values. The result showed significant association between antioxidants intake from traditional Minangfood with some lipid profile after adjusted for some counfounding factors such as gender and age. It was concluded that high level of antioxidant intake from traditional "Minang" food with high-level fiber intake was a potentialprotective factor for CVD risk in ethnic Minang communities.